Alternative futures for ASEAN an educational perspectives - ASEAN Scholars Group
This article outlines the views concerning alternative middle-range cultural features for the five member nations of the Association of Southeast Asian Nations (ASEAN), namely Indonesia, Malaysia, Philippines, Singapore, and Thailand ASEAN aims primarily to secure peace, progress, and well-being for its peoples through regional cooperation in the economic, social, cultural, scientific, and technological fields.
Keywords: ASEAN; Education -- Asia, Southeastern